2020
DOI: 10.1074/jbc.ra120.013696
|View full text |Cite
|
Sign up to set email alerts
|

A myelin basic protein fragment induces sexually dimorphic transcriptome signatures of neuropathic pain in mice

Abstract: In the peripheral nerve, mechanosensitive axons are insulated by myelin, a multilamellar membrane formed by Schwann cells. Here, we offer first evidence that a myelin degradation product induces mechanical hypersensitivity and global transcriptomics changes in a sex-specific manner. Focusing on downstream signaling events of the functionally active 84-104 myelin basic protein (MBP84-104) fragment released after nerve injury, we demonstrate that exposing the sciatic nerve to MBP84-104 via endoneurial injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(63 citation statements)
references
References 73 publications
(173 reference statements)
4
59
0
Order By: Relevance
“…The released dMBP/MBP(69-86) peptide levels and the MBP-degrading protease activity [55] are comparable in female and male CCI nerves, suggesting that sexual dimorphism arises downstream of the MBP epitope action [43]. The equal-dose intraneural MBP(84-104) induces female-speci c mechanical hypersensitivity through a vast and sex-speci c transcriptional reprogramming in the nerves and the corresponding DRG and spinal cord [43]. Among the major multi-systemic changes induced by intraneural MBP(84-104) is sex-speci c changes in lipid-calcium metabolism, T and B cell-related gene activity progressing from the nerve to DRG and spinal cord only in females, but not males [43].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The released dMBP/MBP(69-86) peptide levels and the MBP-degrading protease activity [55] are comparable in female and male CCI nerves, suggesting that sexual dimorphism arises downstream of the MBP epitope action [43]. The equal-dose intraneural MBP(84-104) induces female-speci c mechanical hypersensitivity through a vast and sex-speci c transcriptional reprogramming in the nerves and the corresponding DRG and spinal cord [43]. Among the major multi-systemic changes induced by intraneural MBP(84-104) is sex-speci c changes in lipid-calcium metabolism, T and B cell-related gene activity progressing from the nerve to DRG and spinal cord only in females, but not males [43].…”
Section: Discussionmentioning
confidence: 95%
“…The released dMBP/MBP(69-86) peptide levels and the MBP-degrading protease activity [55] are comparable in female and male CCI nerves, suggesting that sexual dimorphism arises downstream of the MBP epitope action [43]. The equal-dose intraneural MBP(84-104) induces female-speci c mechanical hypersensitivity through a vast and sex-speci c transcriptional reprogramming in the nerves and the corresponding DRG and spinal cord [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After demonstrating that the injection of MBP 84–104 fragment into naïve nerves induced an ipsilateral inflammatory and immune cascade, Liu et al (2012) postulated that nerve injury and repeated exposure of this hidden region on MBP led to a deleterious, allodynia-reinforcing immune reaction (Liu et al, 2012b). Expanding on this, Chernov et al (2018) interestingly demonstrated that sciatic nerve injection of the MBP 84–104 fragment induced long-lasting mechanical allodynia in female, but not male animals (Chernov et al, 2018). Moreover, they also observed sexual dimorphism in gene expression profiles measured in the sciatic nerve, DRG and spinal cord post injection.…”
Section: Scs Modulates Neuroinflammatory Pain Regulationmentioning
confidence: 89%